IMPROVING STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT BY USING MIND MAPPING TECHNIQUE AT SMP SWASTA PENCAWAN MEDAN - krisna pakpahan; Lestari Ayu Br Ginting; Cindy Debora (elt, 2019)
The ability to write is one component of language that is very important in human life. A person's ability to write can express ideas and thoughts to achieve goals and benefits. This study aims to determine the ability of students of class VIII A Medan Pencawan Private Middle School to write descriptive text by using mind mapping techniques. The research subjects consisted of 28 students. This study was conducted by applying two tests The results of research in the Pre-Test that did not.use mind mapping techniques showed that the average value of students ie 34.11 did not meet the KKM. Because students' interest in writing descriptive texts is still low and only a few are enthusiastic. And after the mind mapping technique was applied there was an increase in the learning process of writing descriptive texts. This is indicated by the increasing interest of students and their enthusiasm and the average results on the second test or Post-Test increased to 84.68. Thus, it can be concluded that mind mapping techniques can improve students' writing abilities in descriptive text.